PENERAPAN MODEL PEMBELAJARAN TEAM QUIZ DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI KELAS VIII SMP NEGERI 1 SIDUAORI - Linismawati Laia (Universitas Nias Raya, 2024)
The problem with this study is that students' learning activities and learning outcomes tend to be low. The objective of the study is to determine the application of Team Her Quiz Learning Model to improve learning outcomes of Pancasila and Citizenship Education in Class VIII of SMP Negri 1 Sidhu Aori. This study uses classroom style action research. The study subjects were 18 students of class VIII, and the students' learning outcomes were as follows: In Cycle I, the average student learning outcome was 60.83 points, and the completion rate was 44.44%, and in Cycle II, the average student learning outcome was 60.83 points, and the completion rate was 44.44%. The rate was 44.44%. 'The learning outcome was 76.94 points and the completion rate was 100%. . The conclusion of the study is to apply the team quiz learning model to improve the learning outcomes of Pancasila and citizenship education for class VIII in SMP Negri 1 Sidhu Aori. Researchers have made several suggestions, including: Students should be more courageous in expressing their opinions and asking questions to their friends and teachers, so that interaction between students and teachers will occur and learning will be more active. Teachers need to be more careful in choosing variations in the application of learning models that help develop students' potential. Schools should provide teachers with guidance on the use of active and fun learning models, such as the team quiz learning model, to enable active and fun learning and best achieve learning objectives. Future researchers should further develop this classroom practice research as a research model to improve the quality of learning and enrich the body of knowledge in the field of education.